A study on the level of service quality: case for Northport Malaysia Bhd as Malaysia's world port / Aini Qamariah Mohd Yusof - Mohd Yusof, Aini Qamariah (Faculty of Business and Management, 2007)
This research is about a study on the level of service quality in Northport (M) Bhd as Malaysia's world port. Researcher has found out that to measures service quality, factors such as reliability, tangibles, responsiveness, assurance and empathy are important. However, in this research, researcher decided to choose the critical factors that are reliability, tangibles and responsiveness to measures the level of service quality in Northport (M) Bhd. Based on the annual report of the company for the year 2005 and 2007, a declined of market share has been identified by researcher as the main problem faced by the company. The competitive situation between Northport (M) Bhd and their competitor has been the issue that must be solve. Service quality is one way to help the company in the tough situation. So, the objectives of doing this research is to identify the current level of service quality provided by Northport (M) Bhd to their customers as well as to analyse the strength and weaknesses of Northport (M) Bhd in their port operation. Questionnaires were distributed to the respondents whom the customers of Northport (M) Bhd with vary in background. Simple Random Sampling has been used to select the respondents. The sample size for this research is 80 respondents and researcher used primary and secondary data collection method as well. The Statistical Package for the Social Science (SPSS) version 14.0 has been used for the data interpretation and analysis. The results were in form of reliability testing, frequency, cross tabulations, one way ANOVA and correlation. For overall findings, the results of the level of service quality provided by Northport (M) Bhd is at the medium level. Northport should increase their service quality in order to increase their performance in future.